ANALISIS SWOT UNTUK MENENTUKAN STRATEGI PENANGANAN BARANG JASA TITIP (STUDI KASUS KPU BC TIPE C SOEKARNO-HATTA) - Muchtar, Masruri (Politeknik Keuangan Negara STAN, 2019)
This research aims to determine appropriate strategy conducted by KPU BC Type C Soekarno-Hatta in controlling passenger’s imported good in particularly regarding Jasa Titip (Jastip) service provided in Soekarno-Hatta International Airport due to the role of Directorate General of Customs and Excise as revenue collector and community protector. This research uses the approach of post-positivism to the type of descriptive. The data collection techniques are observation, depth interview, and literature study. This study uses SWOT Analysis. Internal and external factors are identified in the SWOT matrix. Result shows that an integrated information system connected to other authorities’ database enhanced with special feature is highly required. In addition, KPU BC Type C Soekarno-Hatta should have been initially planning the need of sophisticated NPP detection tools and X-Ray machine. The Analyst Teams should upgrade their competencies so that they are able to understand the behavior of Jastip provider in using social media. A program to educate society about import regulations, obligations, and penalties are also need to be prepared. Lastly, a new policy should immediately be made.